Polypropylene composite material, preparation method thereof and application of polypropylene composite material in preparation of balance car
By introducing modified POE as a compatibility agent, it uses its high compatibility with polypropylene, nylon 6 and ultrafine calcium carbonate to solve the problem of poor compatibility between polypropylene, nylon 6 and calcium carbonate, and significantly improves the mechanical properties of polypropylene composite materials.
Patent Information
- Application Number
- CN202510095522.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The poor compatibility between polypropylene, nylon 6 and calcium carbonate leads to insufficient mechanical properties of polyethylene materials.
Modified POE is used as a compatibility agent. By introducing groups such as hydroxyl, ether bonds and amide bonds into POE, the modified POE forms hydrogen bonds and chemical bonds with ultrafine calcium carbonate and nylon 6 to improve its compatibility, and the modified POE is blended with polypropylene, nylon 6 and ultrafine calcium carbonate through melt grafting technology.
The tensile performance, impact strength and bending strength of polypropylene composite materials have been significantly improved, making it better used in high-strength and high-performance children's balance bikes, children's strollers and other products.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polypropylene, and in particular to a polypropylene composite material and a preparation method thereof, and application thereof in the preparation of a balance vehicle. Background Art
[0002] Polypropylene has a transparent appearance, low density, light texture, and good antibacterial, wear resistance, electrical insulation and other advantages. It is widely used in children's balance cars, baby carriages, plastic toys, alloy toys and other products. Nylon 6 has high mechanical strength and good impact resistance. Compounding it with polypropylene can complement the advantages of the two and make an alloy material with excellent performance. Usually, a compatibilizer needs to be added to improve the compatibility between the two.
[0003] POE ethylene-octene copolymer is an elastomeric material with excellent performance. As a polyolefin diamond mesh, it has good compatibility with polypropylene and has important applications in toughening and modification of materials such as polypropylene. The patent with announcement number CN105504512B discloses a shallow shrinkage reinforced polypropylene material and a preparation method thereof. The polypropylene material obtained by using polypropylene, nylon resin, maleic anhydride grafted POE, compatibilizer, etc. as raw materials has the advantages of anti-sinking, scratch resistance, high strength, etc. Compared with the patent, the polypropylene composite material of the present invention has higher tensile properties, impact strength and bending strength. Summary of the invention
[0004] The technical problem solved by the invention is to solve the problem of poor compatibility among polypropylene, nylon 6 and calcium carbonate, and to improve the mechanical properties of polyethylene materials.
[0005] Technical solution: A polypropylene composite material, comprising the following raw materials in parts by weight: 100 parts of polypropylene, 15-30 parts of nylon 6, 5-25 parts of ultrafine calcium carbonate, 8-15 parts of modified POE, and 0.4-0.6 parts of antioxidant.
[0006] Preferably, the preparation method of the polypropylene composite material is: adding modified POE and ultrafine calcium carbonate to a mixer, blending at 75-90° C. for 2-3 hours, then adding polypropylene, nylon 6, and an antioxidant, mixing at 70-80° C. for 40-60 minutes, then adding the blend to a twin-screw extruder, melt blending at 180-235° C., extruding, and injection molding in an injection molding machine at 220-230° C. to obtain a polypropylene composite material.
[0007] Preferably, the preparation method of modified POE is: (1) Add ethylene glycol diglycidyl ether and diimino monomer in a molar ratio of 1: (1-1.1) to tetrahydrofuran, heat to 50-60°C, stir and react for 8-12 hours, distill under reduced pressure, wash with ethanol, and dry to obtain a hydroxy polymer. The preparation reaction formula is: .
[0008] (2) In an ice bath, add hydroxyl polymer, triethylamine, and acryloyl chloride monomer in a mass ratio of 100: (1.7-2.6): (1.5-2.3) to N,N-dimethylformamide, then stir and react at room temperature for 4-6 hours, distill under reduced pressure, wash with ethanol, and dry to obtain an acrylate-based polymer. The reaction formula is: .
[0009] (3) Ethylene-octene copolymer POE, acrylate-based polymer and diisopropylbenzene peroxide in a mass ratio of 100:(4-10):(0.07-0.18) are mixed and melt-grafted at 170-180°C for 7-10 minutes in a torque rheometer. The product is added to xylene and heated to reflux. Then acetone is added. After filtering, the precipitate is extracted with acetone and dried to obtain modified POE.
[0010] Preferably, the acryloyl chloride monomer is acryloyl chloride or methacryloyl chloride.
[0011] Preferably, the preparation method of the diimino monomer is as follows: in an ice bath, N-Boc-N-methylethylenediamine (CAS No. ), triethylamine, and diacyl chloride are added to dichloromethane in a molar ratio of (2-2.2): (2-2.2): 1, and then stirred at room temperature for 6-8 hours, distilled under reduced pressure, washed with water and dried, and the product is added to a 3 mol / L hydrogen chloride ethyl acetate solution, stirred at room temperature for 4-5 hours, the Boc protecting group is removed, distilled under reduced pressure, washed with a saturated sodium carbonate solution, and dried to obtain the diimino monomer. The preparation reaction formula is: .
[0012] Preferably, the structural formula of the diacyl chloride is , a is any integer between 2 and 4.
[0013] Preferably, the polypropylene composite material is used in the preparation of a balance vehicle.
[0014] The technical effect of the present invention is as follows: the present invention conducts epoxy addition polymerization reaction of diimino monomer and ethylene glycol diglycidyl ether to obtain hydroxyl polymer, part of the hydroxyl groups of which react with (meth) acryloyl chloride to obtain acrylate polymer, and the introduced olefin groups are melt-grafted on POE ethylene-octene copolymer to obtain modified POE, thereby introducing polymer molecular chains containing hydroxyl, ether bond and amide bond groups into the side chain of POE.
[0015] The present invention blends polypropylene, nylon 6, ultrafine calcium carbonate, modified POE, etc. to obtain a polypropylene composite material. The hydroxyl and ether bonds of the polymer molecular chain introduced by the side chain grafting of modified POE can form hydrogen bonds, chemical bonds, etc. with the hydroxyl surface of ultrafine calcium carbonate, thereby realizing the surface modification and modification of POE to ultrafine calcium carbonate, and the side chain polymer of modified POE contains a large amount of amide bonds, and has similar polarity with the polyamide molecular chain of nylon 6, so that modified POE and nylon 6 also have good similar compatibility, while modified POE contains a polyolefin main chain, and has a high compatibility with polypropylene, so that modified POE can be used as a compatibilizer, and the compatibility between ultrafine calcium carbonate, nylon 6 and polypropylene is improved at the same time, so that polypropylene and nylon 6 form a compatible alloy system, and ultrafine calcium carbonate has a better reinforcing effect in strength, and modified POE also plays a good toughening effect, and the obtained polypropylene composite material shows higher tensile properties, impact strength and bending strength. There are better practical applications in high-strength and high-performance children's balance cars, baby carriages, plastic toys, alloy toys, etc. DETAILED DESCRIPTION
[0016] The present application is further described in detail below with reference to the embodiments.
[0017] The polypropylene (brand name CHC3007) and nylon 6 (brand name 8202CHS) in the examples are sourced from Dongguan Juona New Materials Co., Ltd.
[0018] POE ethylene-octene copolymer (brand name A4090S) and maleic anhydride grafted POE (brand name MA9015) were sourced from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd.
[0019] Ultrafine calcium carbonate, particle size 2000 mesh, sourced from Lingshou County Yongshun Mineral Products Processing Plant.
[0020] Example 1 (1) In an ice bath, add 30 mmol N-Boc-N-methylethylenediamine, 30 mmol triethylamine and 15 mmol succinyl chloride to 50 mL dichloromethane, and then stir and react at room temperature for 8 h. Distill under reduced pressure, wash with water and dry. Add the product to 70 mL 3 mol / L hydrogen chloride in ethyl acetate solution, stir and react at room temperature for 5 h to remove the Boc protecting group. Distill under reduced pressure, wash with saturated sodium carbonate solution and dry to obtain a diimino monomer.
[0021] (2) Add 40 mmol of ethylene glycol diglycidyl ether and 40 mmol of diimino monomer to 150 mL of tetrahydrofuran, heat to 60°C, stir and react for 10 h, distill under reduced pressure, wash with ethanol, and dry to obtain a hydroxy polymer.
[0022] (3) In an ice bath, 20 g of hydroxy polymer, 0.45 g of triethylamine, and 0.4 g of methacryloyl chloride were added to 250 mL of N,N-dimethylformamide, and the mixture was stirred for reaction at room temperature for 4 h. The mixture was distilled under reduced pressure, washed with ethanol, and dried to obtain an acrylate-based polymer.
[0023] (4) 500 g of ethylene-octene copolymer POE, 20 g of acrylate-based polymer, and 0.35 g of diisopropylbenzene peroxide were mixed and melt-grafted in a torque rheometer at 175 °C for 7 min. The product was added to xylene and heated to reflux. Then acetone was added. After filtering, the precipitate was extracted with acetone and dried to obtain modified POE.
[0024] (5) Add 0.8 kg of modified POE and 0.5 kg of ultrafine calcium carbonate into a mixer, blend at 80 ° C for 2 h, then add 10 kg of polypropylene, 1.5 kg of nylon 6, and 47 g of antioxidant 1010, mix at 70 ° C for 60 min, then add the blend into a twin-screw extruder, melt blend at 180 ° C, 210 ° C, 230 ° C, 235 ° C, 235 ° C, and 225 ° C in sections 1-6, extrude, and injection mold in an injection molding machine, with sections 1-4 at 220 ° C, 230 ° C, 230 ° C, 225 ° C to obtain a polypropylene composite material.
[0025] Comparative Example 1 (1) 0.5 kg of ultrafine calcium carbonate, 10 kg of polypropylene, 1.5 kg of nylon 6, and 47 g of antioxidant 1010 were mixed at 70°C for 60 min, and the mixture was added to a twin-screw extruder. The temperature of sections 1-6 was 180°C, 210°C, 230°C, 235°C, 235°C, and 225°C for melt blending. The mixture was extruded and injection molded in an injection molding machine. The temperature of sections 1-4 was 220°C, 230°C, 230°C, and 225°C to obtain a polypropylene composite material.
[0026] Comparative Example 2 (1) Add 0.8 kg of ethylene-octene copolymer POE and 0.5 kg of ultrafine calcium carbonate into a mixer, blend at 80°C for 2 h, then add 10 kg of polypropylene, 1.5 kg of nylon 6 and 47 g of antioxidant 1010, mix at 70°C for 60 min, then add the blend into a twin-screw extruder, melt blend at 180°C, 210°C, 230°C, 235°C, 235°C and 225°C in sections 1-6, extrude, and injection mold in an injection molding machine, at sections 1-4 at 220°C, 230°C, 230°C and 225°C, to obtain a polypropylene composite material.
[0027] Comparative Example 3 (1) Add 0.8 kg of maleic anhydride grafted POE and 0.5 kg of ultrafine calcium carbonate into a mixer, blend at 80 ° C for 2 h, then add 10 kg of polypropylene, 1.5 kg of nylon 6, and 47 g of antioxidant 1010, mix at 70 ° C for 60 min, then add the blend into a twin-screw extruder, melt blend at 180 ° C, 210 ° C, 230 ° C, 235 ° C, 235 ° C, and 225 ° C in sections 1-6, extrude, and injection mold in an injection molding machine, and the temperatures of sections 1-4 are 220 ° C, 230 ° C, 230 ° C, and 225 ° C to obtain a polypropylene composite material.
[0028] Comparative Example 4 (1) Add 40 mmol of ethylene glycol diglycidyl ether and 40 mmol of N,N'-dimethylethylenediamine to 150 mL of tetrahydrofuran, heat to 60°C, stir and react for 10 h, distill under reduced pressure, wash with ethanol, and dry to obtain a hydroxy polymer.
[0029] (2) In an ice bath, 20 g of hydroxy polymer, 0.45 g of triethylamine and 0.4 g of methacryloyl chloride were added to 250 mL of N,N-dimethylformamide, and the mixture was stirred for reaction at room temperature for 4 h. The mixture was distilled under reduced pressure, washed with ethanol and dried to obtain an acrylate-based polymer.
[0030] (3) 500 g of ethylene-octene copolymer POE, 20 g of acrylate-based polymer, and 0.35 g of diisopropylbenzene peroxide were mixed and melt-grafted in a torque rheometer at 175 °C for 7 min. The product was added to xylene and heated to reflux. Then acetone was added. After filtering, the precipitate was extracted with acetone and dried to obtain modified POE.
[0031] (4) Add 0.8 kg of modified POE and 0.5 kg of ultrafine calcium carbonate into a mixer, blend at 80 ° C for 2 h, then add 10 kg of polypropylene, 1.5 kg of nylon 6, and 47 g of antioxidant 1010, mix at 70 ° C for 60 min, and then add the blend into a twin-screw extruder, melt blend at 180 ° C, 210 ° C, 230 ° C, 235 ° C, 235 ° C, and 225 ° C in sections 1-6, extrude, and injection mold in an injection molding machine, with the temperatures of 1-4 sections being 220 ° C, 230 ° C, 230 ° C, and 225 ° C to obtain a polypropylene composite material.
[0032] Example 2 (1) In an ice bath, add 30 mmol N-Boc-N-methylethylenediamine, 30 mmol triethylamine and 15 mmol adipoyl chloride to 50 mL dichloromethane, and then stir and react for 6 h at room temperature. Distill under reduced pressure, wash with water and dry. Add the product to 80 mL 3 mol / L hydrogen chloride in ethyl acetate solution, stir and react for 4 h at room temperature to remove the Boc protecting group. Distill under reduced pressure, wash with saturated sodium carbonate solution and dry to obtain a diimino monomer.
[0033] (2) Add 40 mmol of ethylene glycol diglycidyl ether and 44 mmol of diimino monomer to 150 mL of tetrahydrofuran, heat to 60°C, stir and react for 8 h, distill under reduced pressure, wash with ethanol, and dry to obtain a hydroxy polymer.
[0034] (3) In an ice bath, 20 g of hydroxy polymer, 0.52 g of triethylamine, and 0.46 g of acryloyl chloride were added to 300 mL of N,N-dimethylformamide, and the mixture was stirred for reaction at room temperature for 6 h. The mixture was distilled under reduced pressure, washed with ethanol, and dried to obtain an acrylate-based polymer.
[0035] (4) 500 g of ethylene-octene copolymer POE, 35 g of acrylate-based polymer, and 0.62 g of diisopropylbenzene peroxide were mixed and melt-grafted in a torque rheometer at 180°C for 7 min. The product was added to xylene and heated to reflux. Then acetone was added. After filtering, the precipitate was extracted with acetone and dried to obtain modified POE.
[0036] (5) Add 1.2 kg of modified POE and 1.8 kg of ultrafine calcium carbonate into a mixer and blend at 75 °C for 3 h. Then add 10 kg of polypropylene, 2.3 kg of nylon 6 and 40 g of antioxidant 1010 and mix at 80 °C for 40 min. Then add the blend into a twin-screw extruder and melt blend at 180 °C, 210 °C, 230 °C, 235 °C, 235 °C and 225 °C in sections 1-6. Extrude and injection mold in an injection molding machine at sections 1-4 at 220 °C, 230 °C, 230 °C and 225 °C to obtain a polypropylene composite material.
[0037] Example 3 (1) In an ice bath, add 33 mmol N-Boc-N-methylethylenediamine, 33 mmol triethylamine and 15 mmol glutaryl chloride to 50 mL dichloromethane, and then stir and react for 6 h at room temperature. Distill under reduced pressure, wash with water and then dry. Add the product to 70 mL 3 mol / L hydrogen chloride in ethyl acetate solution, stir and react for 5 h at room temperature to remove the Boc protecting group. Distill under reduced pressure, wash with saturated sodium carbonate solution and dry to obtain a diimino monomer.
[0038] (2) Add 40 mmol of ethylene glycol diglycidyl ether and 40 mmol of diimino monomer to 150 mL of tetrahydrofuran, heat to 50°C, stir to react for 12 h, distill under reduced pressure, wash with ethanol, and dry to obtain a hydroxy polymer.
[0039] (3) In an ice bath, 20 g of hydroxy polymer, 0.34 g of triethylamine, and 0.3 g of methacryloyl chloride were added to 250 mL of N,N-dimethylformamide, and the mixture was stirred for reaction at room temperature for 4 h. The mixture was distilled under reduced pressure, washed with ethanol, and dried to obtain an acrylate-based polymer.
[0040] (4) 500 g of ethylene-octene copolymer POE, 50 g of acrylate-based polymer, and 0.9 g of diisopropylbenzene peroxide were mixed and melt-grafted in a torque rheometer at 170 °C for 10 min. The product was added to xylene and heated to reflux. Then acetone was added. After filtering, the precipitate was extracted with acetone and dried to obtain modified POE.
[0041] (5) Add 1.5 kg of modified POE and 2.5 kg of ultrafine calcium carbonate into a mixer, blend at 90 ° C for 2 h, then add 10 kg of polypropylene, 3 kg of nylon 6, and 60 g of antioxidant 1010, mix at 70 ° C for 60 min, then add the blend into a twin-screw extruder, melt blend at 180 ° C, 210 ° C, 230 ° C, 235 ° C, 235 ° C, and 225 ° C in sections 1-6, extrude, and injection mold in an injection molding machine, with sections 1-4 at 220 ° C, 230 ° C, 230 ° C, 225 ° C to obtain a polypropylene composite material.
[0042] The tensile properties are tested according to the national standard GB / T 1040.1-2018. The impact strength is tested according to the national standard GB / T 1043.1-2008. The flexural strength is tested according to the national standard GB / T 9341-2000.
[0043] Table 1 Mechanical properties test of polypropylene composites Tensile strength (MPa) Elongation at break (%) <![CDATA[Impact strength (kJ / m 2 )]]> Bending strength (MPa) Example 1 35.1 472.6 16.4 50.6 Comparative Example 1 32.4 372.0 8.1 41.7 Comparative Example 2 30.3 403.9 10.8 44.3 Comparative Example 3 36.8 442.1 13.5 48.2 Comparative Example 4 31.9 453.8 11.9 47.8 Example 2 42.0 626.7 31.5 64.4 Example 3 31.3 605.6 33.8 57.0
[0044] Compared with Comparative Example 1, Example 1 adds modified POE, and the polymer molecular chain introduced by its side chain grafting contains groups such as hydroxyl, ether bond and amide bond, and hydroxyl and ether bond can form hydrogen bonds, chemical bonds and other interactions with the hydroxyl surface of ultrafine calcium carbonate, thereby realizing the surface modification and modification of ultrafine calcium carbonate by POE, and POE contains a large number of amide bonds, and has similar polarity to the polyamide molecular chain of nylon 6, so that modified POE has good similar compatibility with nylon 6, and modified POE contains a polyolefin main chain, and has high compatibility with polypropylene, so that modified POE can be used as a compatibilizer, and at the same time improves the compatibility between ultrafine calcium carbonate, nylon 6 and polypropylene, so that polypropylene and nylon 6 form a compatible alloy system, and ultrafine calcium carbonate has a better reinforcement effect, and modified POE also plays a good toughening effect, and the obtained polypropylene composite material shows higher tensile properties, impact strength and bending strength. Example 2-3 regulates the ratio of raw materials, and the obtained polypropylene material also has good mechanical properties.
[0045] In Comparative Example 2, only ethylene-octene copolymer POE was added, which could not play the role of a compatibilizer and could not improve the compatibility between ultrafine calcium carbonate, nylon 6 and polypropylene, resulting in poor mechanical properties such as tensile strength of the polypropylene composite material.
[0046] In Comparative Example 3, maleic anhydride grafted POE is added, and the anhydride groups contained in it can react with ultrafine calcium carbonate and the terminal amino group of nylon 6 to improve the compatibility between the two and polypropylene. The tensile strength and other mechanical properties of the polypropylene material are significantly higher than those of Comparative Example 1, but its elongation at break and impact strength are significantly lower than those of Example 1. It may be that the side chain of the modified POE in Example 1 introduces a flexible polyether molecular chain, which has a better toughening effect, is conducive to improving toughness, and exhibits higher elongation at break and impact strength.
[0047] In Comparative Example 4, N,N'-dimethylethylenediamine is used as the reactant, and the molecular chains of the prepared hydroxyl polymer and acrylate-based polymer do not contain amide bonds. After melt grafting of POE, the side chains of the modified POE obtained do not contain amide bonds, and the compatibility with nylon 6 is poor. The compatibility between nylon 6 and polypropylene cannot be improved, and a compatible alloy system is not formed, resulting in low mechanical properties such as tensile strength of the composite material.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polypropylene composite material, characterized in that: The following raw materials are included by weight: 100 parts of polypropylene, 15-30 parts of nylon 6, 5-25 parts of ultrafine calcium carbonate, 8-15 parts of modified POE, and 0.4-0.6 parts of antioxidant; The preparation method of the modified POE is: (1) Add ethylene glycol diglycidyl ether, structural formula: The diimino monomer, wherein n is any integer from 2 to 4, is heated to a reaction temperature, stirred for reaction, distilled under reduced pressure, washed with ethanol, and dried to obtain a hydroxy polymer; (2) adding a hydroxy polymer, triethylamine and acryloyl chloride monomer to N,N-dimethylformamide under an ice bath, and then stirring the mixture at room temperature for 4-6 hours, distilling under reduced pressure, washing with ethanol, and drying to obtain an acrylate-based polymer; (3) Ethylene-octene copolymer POE, acrylate-based polymer and diisopropylbenzene peroxide are mixed and melt grafted in a torque rheometer. The product is added to xylene and heated to reflux. Then acetone is added. After filtering, the precipitate is extracted with acetone and dried to obtain modified POE.
2. The polypropylene composite material according to claim 1, characterized in that: The reaction temperature in (1) is 50-60°C and the reaction time is 8-12h.
3. The polypropylene composite material according to claim 1, characterized in that: The molar ratio of ethylene glycol diglycidyl ether to diimino monomer in (1) is 1:(1-1.1).
4. The polypropylene composite material according to claim 3, characterized in that: The preparation method of the diimino monomer is as follows: in an ice bath, N-Boc-N-methylethylenediamine, triethylamine and diacyl chloride are added in a molar ratio of (2-2.2): (2-2.2): 1 to dichloromethane, and then stirred at room temperature for 6-8 hours, distilled under reduced pressure, washed with water and then dried, and the product is added to an ethyl acetate solution of hydrogen chloride, stirred at room temperature for 4-5 hours, distilled under reduced pressure, washed with a saturated sodium carbonate solution, and dried to obtain the diimino monomer.
5. The polypropylene composite material according to claim 4, characterized in that: The structural formula of the diacyl chloride is , a is any integer between 2 and 4.
6. The polypropylene composite material according to claim 1, characterized in that: The mass ratio of the hydroxy polymer, triethylamine and acryloyl chloride monomer in (2) is 100:(1.7-2.6):(1.5-2.3); the acryloyl chloride monomer is acryloyl chloride or methacryloyl chloride.
7. The polypropylene composite material according to claim 1, characterized in that: The mass ratio of hydroxyethylene-octene copolymer POE, acrylate-based polymer and diisopropylbenzene peroxide in (3) is 100:(4-10):(0.07-0.18).
8. The polypropylene composite material according to claim 1, characterized in that: The temperature during melt grafting in (3) is 170-180°C and the time is 7-10 minutes.
9. A method for preparing a polypropylene composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: adding modified POE and ultrafine calcium carbonate into a mixer, blending at 75-90° C. for 2-3 hours, then adding polypropylene, nylon 6 and an antioxidant, mixing at 70-80° C. for 40-60 minutes, adding the blend into a twin-screw extruder, melt blending at 180-235° C., extruding, and injection molding at 220-230° C. in an injection molding machine to obtain a polypropylene composite material.
10. Use of the polypropylene composite material obtained by the preparation method according to claim 9 in preparing a self-balancing vehicle.
Citation Information
Patent Citations
A shallow sink mark reinforced polypropylene material and its preparation method
CN105504512B
Toughened modified nylon
CN109504084A
Flame-retardant antistatic polyamide composite material and preparation method thereof
CN110204897A
High-impact-toughness polyamide 6 composite material and preparation method thereof
CN118515969A
Polypropylene composite material capable of blasting at low temperature, and preparation method therefor and application thereof
WO2022242297A1
Cited By
Modified inorganic ultrafine particle reinforced and toughened PP composite material
CN121495245A